Quantum Mechanics (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
Quantum mechanics has brought a gigantic breakthrough to physics since its introduction more than a century ago. It has led to many discoveries at the microscopic level, initiated new pathways to unsuspected properties of matter, and produced new and amazing usable applications. This Special Issue of Symmetry is devoted to recent advances in theoretical developments in quantum mechanics. It is part of the global effort to provide a continuous supply of information to the research community. This volume gathers contributions in various directions and their contents are best described chronologically by their abstracts, which are hereafter listed for the convenience of the reader.